First observations of ecological surveillance plots on afforested open-cast spoil in South Wales - Dawkins, H; Hockin, R; Power, J (Commenwealth Forestry Institute, University of Oxford, 1985)
The object of this project was to initiate a long-term study of the development of soil, vegetation and fauna on 'restored', afforested open-cast sites in the South Wales coalfield. The task was to establish and observe 'permanently' detectable, subjectively sited plots~ marked by durable underground steel rods, precisely positioned by National Grid co-ordinates. Records were designed to be accessible and intelligible for recurrent observation, by any observers who might be in touch with any institution where these observations are lodged...